Intraoral CD30+ T-Cell Lymphoproliferative Disorder with Lymphomatoid Papulosis Type C Features Mimics Lymphoma Histopathologically and Immunohistochemically - Barbeiro, Camila Oliveira [UNESP]; Silveira, Heitor Albergoni; Barbeiro, Roberto Henrique [UNESP]; Martins, Karina Helen; Bufalino, Andreia [UNESP]; Chahud, Fernando; León, Jorge Esquiche (Springer Nature, 2024)
Background: Previous studies have shown that at least a of intraoral eosinophilic ulcer is best classified as a CD30 + T-cell lymphoproliferative disorder (LPD), with histopathology reminiscent of lymphomatoid papulosis (LyP) of the skin. Microscopically, a mixed population of inflammatory cells, often including eosinophils and varying numbers of atypical lymphoid cells, frequently expressing CD30, is typical for LyP, whose clinicopathological spectrum includes type A, B, C, D, E, and LyP with DUSP22/IRF4 rearrangement. To date, about 27 intraoral LyP cases have been reported. Of them, 7 cases were diagnosed as LyP type C, which is frequently confused with anaplastic large cell lymphoma (ALCL) on histopathology. Methods: A 60-year-old male was referred for a one-month history of a tongue ulcer. Results: Microscopy showed numerous subepithelial atypical large lymphoid cells, which expressed CD4 (with partial loss of CD3, CD5, and CD7), CD8 (few cells), CD30 (about 50%, in non-diffuse pattern with size variability), TIA-1, and Ki-67 (85%), without staining for CD56, ALK, LMP1, and EBER1/2, concerning for a diagnosis of ALCL. However, after three weeks, the lesion completely healed. Conclusion: We present here a rare case of intraoral CD30+ T-cell LPD that we believe is the oral counterpart of cutaneous LyP type C.
Keywords: Anaplastic large cell lymphoma; Differential diagnosis; Lymphomatoid papulosis type C; Lymphoproliferative disorder; Oral cavity